SOLUTION OF MICROECONOMICS ASSIGNMENTS BY THE MEANS OF PROGRAM MODULES ISPEZ ON THE DISTANCE PLATFORM MOODLE - V. М. Kobets (Kherson State University, 2010)
In article basic aspects introduction integrated environment verification knowledge students from microeconomic are expounded. It is considered structure of Decision Environmental with the built-in program modules (mathematical and graphical editors) for the decision of typical assignments from microeconomics during the current and final control of students' knowledges of different forms of teaching.